Investigating burn cases, knowledge, attitudes and practices to burn care and prevention in Ethiopia: a community-survey. (2021) - Denekew, Baye; Hebron, Caitlin; Mekonnen, Abeba; Ayele, Mihret; Negash, Kassahun; Desalegne, Muluken; Price, Patricia; Potokar, Tom
No abstract available